Prevalence and genetic characteristics of porcine reproductive and respiratory syndrome virus in central China during 2016–2017: NADC30-like PRRSVs are predominant. (October 2019) - Guo, Zhenhua; Chen, Xin-xin; Li, Xiang; Qiao, Songlin; Deng, Ruiguang; Zhang, Gaiping
Abstract: NADC30-like strains of porcine reproductive and respiratory syndrome virus (PRRSV) were firstly reported in China in 2013. Since then, these strains have been epidemic in more than 13 provinces/regions. During 2016–2017, a total of 18 PRRSV isolates were obtained from 52 clinical samples in Henan province. Based on comparative and phylogenetic analyses of ORF5 and partial Nsp2 genes, 83.3% (15/18) isolates belonged to NADC30-like strains, and the ORF5 shared 87.4%–95.5% nucleotide identity with NADC30/JL580 and 84.2%–89.9% with JXA1/CH-1a, respectively. The genetic variation analysis showed that extensive amino acid substitutions happened in the significant regions of ORF5 including major linear antigenic epitopes (27-30aa, 37-45aa, 52-61aa) and the potential N-glycosylation sites (32-35aa). 16.7% (3/18) isolates were very close to HP-PRRSV derived attenuated strains. Moreover, these three isolates shared common residues at the positions 33D, 59 N, 164R, 196R in ORF5 and 303D, 399T, 575V, 598R, 604G in Nsp2, which were thought to be unique to modified live vaccines (MLVs) or their derivatives. Therefore, they were probably the revertants from MLVs. Our studies showed that the HP-PRRSV strains seemed to be gradually disappearing and NADC30-like strains had become the main causative agents of PRRS in central China. Comparing with HP-PRRSVs, the ORF5 of NADC30-like PRRSV strains displayed extensive amino acid mutations which may be related with immune evasion. Furthermore, the circulation of MLV derivatives in the fields made the diagnosis and control of PRRSV more complicated. Highlights: The clinical PRRS cases were mainly caused by NADC30-like PRRSVstrains in central China. The ORF5 genes had extensive amino acid substitutions in signal peptide, major linear epitopes and N-glycosylation sites. The circulation of MLV derivatives made the diagnosis and control of PRRSV more complicated in China.